Carbon nanotubes as catalysts for wet peroxide oxidation: structure-reactivity relationships - Ribeiro, Rui (2015)
Magnetic neat and N-doped carbon nanotubes with different properties have been synthesized by chemical vapour deposiüon and tested in the catalytic wet peroxide oxidation of 4-nitrophenol solutions (5 g L') at relatively mild operating conditions (atmospheric pressure, T = 50 °C, pH = 3)~using a catalyst load = 2.5 g L-' and [H202]o = 17.8 g L-1. The results demonstrate that the catalyst hydrophobicity/ hydrophilicity is a detenninant property in the CWPO reaction, since it affects the rate ofH202 decomposition. The controlled formation ofreactive radicais (HO* and HOO*) at hydrophobic surfaces avoids the formation of non-reactive species (02 and H20), increasing.